Effect of moisture and freezing on some physical properties of clay soils from plough layer - Kivisaari, Simo (Agricultural and Food Science, 1979)
The aim of this study was to elucidate the effects of freezing on some structural properties of clay soils. The laboratory analyses were based on field observations including measurements of soil temperature and frost depth. The daily temperatures showed remarkable variations on the very soil surface both in the autumn and spring, ranging from below zero at night-time to above 10°C at daytime. The depth of soil frost was deepest in the ploughed field, whilst the straw cowers on the soil surface not only strongly reduced its depth, but also slowed up the thawing. Eight clay soil samples were analyzed in the laboratory. At the potentials of —0.001 to —0.1 bar the water retention capability of soil was reduced by freezing. Disruption of the 5 —10 mm aggregates by freezing, analyzed with wet and dry sievings and waterdrop analysis was strongly dependent on the water potential, the Water potential of 1.0 bar or lower having in general no effect. The total pore volume of aggregates Was dependent on the water potential when it exceeded —15.0 bar. Freezing had a minor effect on the pore volume of the aggregates, if they were let to thaw before drying. The freeze-dried aggregates showed a clear increase of pore volume when the water potential at freezing exceeded —1.0 bar. The movement of water due to ice formation was studied with small and big soil cylinders. It showed a great effect on the structure, if total pore volume, determined with a mercury method, is considered the standard of judgement. Thus it was concluded that the water movement even at a short freezing period is one of the most essential factors determining the structural formation of ploughed clay soil.